Fluorescence Image-Guided Navigation Surgery Using Indocyanine Green for Hepatoblastoma - Eiso Hiyama (MDPI AG, 2021)
In the past decade, navigation surgery using fluorescent indocyanine green (ICG) dye for hepatoblastoma (HB) has been developed for the resection of primary or metastatic tumors. Since HB cells can take up ICG but cannot excrete it to the bile duct, ICG remains in the HB cells, which can be used for navigation by fluorescent activation. The complete resection of the primary tumor as well as metastatic tumors, along with appropriate neoadjuvant and adjuvant chemotherapy, is essential for cure. ICG fluorescence can detect microscopic residual lesions in the primary lesion and identify micro-metastases in the lung or other lesions; consequently, ICG navigation surgery may improve outcomes for patients with HB. The basic technique and recent advances in ICG navigation for HB surgery are reviewed.